2003
DOI: 10.1007/s00421-003-0863-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise duration and mode on the growth hormone responses in young women on oral contraceptives

Abstract: Previous research is conflicting concerning the minimum time duration needed to elicit a growth hormone (GH) response to aerobic exercise; thus, the purpose of this project was to examine the effects of mode and duration on exercise-induced GH responses in young women taking oral contraceptives. Nine healthy young females on oral contraceptives exercised at 75% of their mode-specific peak aerobic power ( VO(2)peak) on the treadmill and cycle ergometer for 10, 15 and 20 min, with serial blood samples taken at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
(84 reference statements)
0
5
1
Order By: Relevance
“…Earlier work (23,24) has demonstrated that GH secretion increased during either short-duration maximal or prolonged submaximal exercise, but was significantly blunted in older men in comparison with their younger counterparts. Likewise we revealed that 30 min of exercise results in a significant increase in GH levels in postmenopausal black and white women, but compared with 20 min of submaximal exercise in younger premenopausal women this response is substantially lower than what we have reported previously (25). Although exercise appears to result in a significant increase in GH levels, it should be noted that 25% of the women had less than a 25% increase in the integrated GH concentrations over the resting day regardless of race or HRT use.…”
Section: Effects Of Race On Gh Concentrationscontrasting
confidence: 76%
“…Earlier work (23,24) has demonstrated that GH secretion increased during either short-duration maximal or prolonged submaximal exercise, but was significantly blunted in older men in comparison with their younger counterparts. Likewise we revealed that 30 min of exercise results in a significant increase in GH levels in postmenopausal black and white women, but compared with 20 min of submaximal exercise in younger premenopausal women this response is substantially lower than what we have reported previously (25). Although exercise appears to result in a significant increase in GH levels, it should be noted that 25% of the women had less than a 25% increase in the integrated GH concentrations over the resting day regardless of race or HRT use.…”
Section: Effects Of Race On Gh Concentrationscontrasting
confidence: 76%
“…Most studies investigating the influence of exercise duration have focused on the minimal exercise duration required to stimulate GH release. Results suggest a range of values, from <10 min to >15 min of exercise being required to elicit an initial rise in GH release (8,11,21,22,24,29,30,32). The inconsistencies in the findings are probably due to differences in the exercise intensity employed in different studies.…”
mentioning
confidence: 93%
“…The early studies in this area demonstrated that both continuous and intermittent exercise results in increased GH concentrations, and a significant increase does not appear until approximately 15 min into exercise [10,11]. Considerable controversy has existed about the optimal exercise intensity for GH release.…”
Section: Exercise and Growth Hormone Responsesmentioning
confidence: 96%